A study of ultrasonic car braking system - Sahri, Mohd Shahrizan (2007)
An ultrasonic car braking system includes; an ultrasonic wave emitter provided in a front portion of an automatic braking car producing and emitting ultrasonic waves frontward in a predetermined distance in front of the car. Ultrasonic receiver also formed in a front portion of the car operatively receiving a reflective ultrasonic wave signal as reflected by obstacles positioned within the pre-determined distance in front of the automatic braking car. The reflected wave (detection pulse) was measured to get the distance between the vehicle and the obstacle. Then PIC is used to control servo motor based on detection pulse information to push pedal brake to brake the car intermittently for automatically braking the car for a safe braking purpose.